Bis[4-(dimethyl-amino)pyridinium] tetra-bromidodiphenyl-stannate(IV). - Yap, Q.L.; Lo, K.M.; Ng, Seik Weng (International Union of Crystallography, 2008)
The Sn(IV) atom of the stannate anion in the title salt, (C(7)H(11)N(2))(2)[SnBr(4)(C(6)H(5))(2)], lies on a center of inversion in a tetra-gonally compressed octa-hedron. The two independent Br atoms in the anion are hydrogen-bond acceptors for the same cation.